Ionic conductivity studies of PEO based polymer electrolyte : PEO + LiBF4 + Si02 / Lili Widarti Zainuddin. - Zainuddin, Lili Widarti (2008)
In this study, PEO will be used as polymer host while lithium tetrafluoroborate (LiBF4) as the inorganic salt and silicon oxide (Si02) as the nanofiller. Films that will be prepared in this study are pure PEO and complexes of PEO + LiBF4 system and PEO + LiBF4 +Si02 system. These studies will be carried out to determine the ionic conductivity of the polymer electrolyte by added salt and nanosize filler. The various percentages of filler that could enhance the conductivity values of the salted samples were determined. Impedance spectroscopy will be used to measure each sample prepared.